Dilema Petani, Diantara Keanggotaan Asosiasi dan Pemenuhan Kebutuhan Hidup (Studi Kasus Petani Kopi Kecamatan Dampit Kabupaten Malang) - Kristiyanto, Sony; Putri Nugroho, Ayu Davieta (Economie: Jurnal Ilmu Ekonomi, 2022)
Indonesia is an agricultural country and one of Indonesia's mainstay agricultural products is coffee. In general, Indonesia's coffee production is the fourth largest in the world. Until now, there are still many coffee plantations with traditional management systems that result in the production and quality of the coffee beans produced being not optimal. Coffee farmers themselves are quite aware of this, and some of them are trying to form farmer associations and with these associations, they can share knowledge about good coffee cultivation. The problem that arises is the gap between farmers who are members of the association and farmers who are not members of the association. This study aims to answer why farmers are still reluctant to join associations that clearly provide a higher level of welfare. This study took place in Dampit District, Malang Regency because in this area there are still clear differences about farmers who are members of the association and farmers who are not members of the association. This study uses a qualitative approach with a phenomenological paradigm. The final conclusion of this study is the ignorance of farmers and the requirements of the association are the two main reasons why there are still farmers who are reluctant to join the association.